2010
DOI: 10.1509/jppm.29.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Foods and Beverages in Schools: The Effect of School Food Policy on Students’ Overweight Measures

Abstract: Beginning with the 2006-2007 academic year, the U.S. government required that all federally funded schools have local wellness policies to promote healthful living and reduce obesity among their students; however, little evidence exists on which school food policies are effective. This article finds evidence that prohibiting à la carte junk food sales during meals reduces the likelihood that students will be overweight or obese by 18 percentage points. The data are merged student-parent-school survey responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Numerous educational marketing campaigns raise children's awareness of the benefits of good nutrition and exercise, and some children are concerned about sustainability issues such as wasteful consumption and environmental degradation [21]. Francis and Davis [4] develop a scale to measure adolescents' sustainability concerns (ASC).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Numerous educational marketing campaigns raise children's awareness of the benefits of good nutrition and exercise, and some children are concerned about sustainability issues such as wasteful consumption and environmental degradation [21]. Francis and Davis [4] develop a scale to measure adolescents' sustainability concerns (ASC).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…9,13 Specific policy solutions for reducing obesity include regulating the food environment by restricting competitive food and fundraiser sales, 1416 using price incentives and other strategies to engage students in healthy eating, 13,17,18 and eliminating advertisements for unhealthy products in schools. 13,19 School policies related to the availability of healthy food are a plausible mechanism by which disparities in obesity and related health behaviors might arise. However, little is known about how policies and practices vary at the school level by geography, socioeconomic status, and racial and economic composition of students at the school.…”
Section: Introductionmentioning
confidence: 99%
“…Dialogue on the topic has been limited by the lack of longitudinal evidence regarding the association between school nutrition policies and student weight status. Research has suggested that competitive food policies are associated with improvements in the school food environment, student dietary intake, or weight outcomes, [28][29][30][31][32][33][34] but most studies were cross-sectional or limited to individual states. A recent study reported no association between competitive food sales and weight gain, but it was based on school administrator surveys rather than independent review of codified laws.…”
mentioning
confidence: 99%